Optimization of the extraction process parameter to obtain highest anti-cancer activity from kenaf seeds - Amid, Azura; Jamal, Parveen; Mohamad, Nurul Elyani; Engku Abdullah, Engku Hasmah (IIUM Press, 2011)
Kenaf (Hibiscus cannabinus) is composed of various active components including tannins, polyphenolics, alkaloids, essential oils and steroids. In this study, kenaf seeds oil was used as a material in observing the anticancer activity on MCF-7 cancer cell line and finding the optimum parameter to extract the oil that give the highest anticancer activity. Kenaf variety Khon kaen seeds were extracted using Supercritical Fluid Extractor (SFE). The extraction was done at the different level of temperature and pressure which range from 40 to 80°C and 200 to 600 bars respectively. Among these two parameters, temperature shows the highest impact on the percentage viability ofMCF-7 breast cancer cell line. All the oils were cytotoxic towards MCF-7 breast cancer cell line in dose dependent manner as detected using the SRB assay. Kenaf seeds oil extracted from SFE at temperature of 40°C and pressure of 400 bars was the most cytotoxic towards MCF-7 breast cancer cell line with the IC50 value of 321.43 ug/ml.